Spanish : an essential grammar - Bradley, Peter T., 1943- (Essential grammar., 2004)
Spanish: An Essential Grammar is a concise and user friendly reference guide to the most important aspects of Spanish. It presents a fresh and accessible description of the language that combines traditional and function-based grammar. The book sets out the complexities of Spanish in short, readable sections, and explanations are clear and free from jargon. The Grammar is the ideal reference source for the learner and user of Spanish. It is suitable for either independent study or for students in schools, colleges, universities and adult classes of all types. Features include: Clear distinctions between the essential and basic aspects of Spanish grammar and those that are more complex; Full use of authentic examples; Easy to understand explanations of areas that customarily pose problems for English speakers; Detailed contents list and index for easy access to information.